Effects of the Menstrual Cycle on Serum Carnitine and Endurance Performance of Women - Matsuda, Tomoka; Furuhata, Tamaki; Ogata, Hazuki; Kamemoto, Kayoko; Yamada, Mizuki; Sakamaki-Sunaga, Mikako (International Journal of Sports Medicine, 2020)
This study aimed to investigate the effect of the menstrual cycle on serum carnitine and the endurance performance of healthy women. Fifteen eumenorrheic women underwent cycle ergometer exercise at 60% maximal oxygen uptake (V̇ O2max) for 45 min, followed by exercise at an intensity that was increased to 80% V̇ O 2max until exhaustion, during two menstrual cycle phases, including the early follicular phase (FP) and the midluteal phase (LP). The blood levels of estradiol, progesterone, total carnitine, free carnitine, and acylcarnitine were assessed. Compared with the FP, the LP had significantly lower serum total carnitine (p<0.05) and free carnitine (p<0.01). Moreover, the group with decreased endurance performance in the LP than in the FP showed a significantly higher change in serum free carnitine compared with the group that showed improved endurance performance in the LP than in the FP (p<0.05). The results of this study suggested that the changes in serum free carnitine during the menstrual cycle might influence endurance performance.
Keywords: estrogen; carnitine; lipid metabolism; early follicular phase; mid luteal phase